Modifying the Siderophore Triacetylfusarinine C for Molecular Imaging of Fungal Infection - Kaeopookum, Piriya; Summer, Dominik; Pfister, Joachim; Orasch, Thomas; Lechner, Beatrix E; Petrik, Milos; Novy, Zbynek; Matuszczak, Barbara; Rangger, Christine; Haas, Hubertus; Decristoforo, Clemens (Molecular imaging and biology, 2019)
PURPOSE: Aspergillus fumigatus produces the siderophore triacetylfusarinine C (TAFC) for iron acquisition which is essential for its virulence. Therefore, TAFC is a specific marker for invasive aspergillosis. We have shown previously that positron emission tomography (PET) imaging with [68Ga]TAFC exhibited excellent targeting properties in an A. fumigatus rat infection model. In this study, we aimed to prepare TAFC analogs modifying fusarinine C (FSC) by acylation with different carbon chain lengths as well as with charged substituents and investigated the influence of introduced substituents on preservation of TAFC characteristics in vitro and in vivo. PROCEDURES: Fifteen TAFC derivatives were prepared and labeled with gallium-68. In vitro uptake assays were carried out in A. fumigatus under iron-replete as well as iron-depleted conditions and distribution coefficient was determined. Based on these assays, three compounds, [68Ga]tripropanoyl(FSC) ([68Ga]TPFC), [68Ga]diacetylbutanoyl(FSC) ([68Ga]DABuFC), and [68Ga]trisuccinyl(FSC) ([68Ga]FSC(suc)3), with high, medium, and low in vitro uptake in fungal cultures, were selected for further evaluation. Stability and protein binding were evaluated and in vivo imaging performed in the A. fumigatus rat infection model. RESULTS: In vitro uptake studies using A. fumigatus revealed specific uptake of mono- and trisubstituted TAFC derivatives at RT. Lipophilicities as expressed by logD were 0.34 to - 3.80. The selected compounds displayed low protein binding and were stable in PBS and serum. Biodistribution and image contrast in PET/X-ray computed tomography of [68Ga]TPFC and [68Ga]DABuFC were comparable to [68Ga]TAFC, whereas no uptake in the infected region was observed with [68Ga]FSC(suc)3. CONCLUSIONS: Our studies show the possibility to modify TAFC without losing its properties and specific recognition by A. fumigatus. This opens also new ways for multimodality imaging or theranostics of fungal infection by introducing functionalities such as fluorescent dyes or antifungal moieties.
Keywords: Protein Binding; železité sloučeniny; tkáňová distribuce; Positron Emission Tomography Computed Tomography; mutace; Mycoses; Blood Proteins; Ferric Compounds; Tissue Distribution; radioizotopy galia; myši inbrední BALB C; Pulmonary Aspergillosis; mykózy; PET; Hydroxamic Acids; Mice, Inbred BALB C; Aspergillus fumigatus; Molecular Imaging; krysa rodu Rattus; siderofory; vazba proteinů; Infection imaging; Animals; krevní proteiny; lidé; plicní aspergilóza; Triacetylfusarinine C; Gallium Radioisotopes; Humans; Gallium-68; zvířata; kyseliny hydroxamové; Rats; PET/CT; molekulární zobrazování; Mutation; Siderophores